Successful Treatment of Left Ventricle Inferior Wall Perforation and Rupture Associated with an Impella 5.5: A Case Report - James Hall; Hasnayn Raza; Sarah Lee; Nicole Bryce; Sunil Abrol (Reports, 2025)
Background and Clinical Significance: Perforation of the left ventricle related to microaxial ventricular assist devices (Impella) is a rare but fatal complication related to placement or adjustment. It results in left ventricular hemorrhage and tamponade, leading to rapid deterioration and death. Case Presentation: We present a case report of a 73-year-old man who developed this complication postoperatively and was successfully managed to a full recovery. Conclusions: To our knowledge, he is the only reported patient to have this complication outside the setting of immediate placement who subsequently survived to discharge.